2015
DOI: 10.1007/s13277-015-3159-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABO gene polymorphism (rs505922) and cancer risk: a meta-analysis

Abstract: Previous studies have showed that ABO blood type is associated with multiple gastrointestinal cancers, including pancreatic cancer. Recently, one single nucleotide polymorphism (SNP) rs505922 in ABO gene has been implicated in susceptibility to pancreatic cancer across different populations, but different results were found in other types of cancer. This meta-analysis aimed to clarify the association. All eligible case-control studies were identified by searching through PubMed and Chinese language databases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Our genotyping analysis showed that T and C alleles of rs505922 and corresponding genotypes are distributed equally between the obese and control groups. The results of allele and genotype frequencies in our study are also comparable to the results obtained in previous studies with T allele ranging from 59 to 62% [30]. Interestingly, a recent meta-analysis provided some evidence that ABO rs505922 SNP C allele is a risk factor for cancer susceptibility, specifically for pancreatic cancer [30].…”
Section: Discussionsupporting
confidence: 90%
“…Our genotyping analysis showed that T and C alleles of rs505922 and corresponding genotypes are distributed equally between the obese and control groups. The results of allele and genotype frequencies in our study are also comparable to the results obtained in previous studies with T allele ranging from 59 to 62% [30]. Interestingly, a recent meta-analysis provided some evidence that ABO rs505922 SNP C allele is a risk factor for cancer susceptibility, specifically for pancreatic cancer [30].…”
Section: Discussionsupporting
confidence: 90%
“…These findings have been validated in multiple populations, including American, Han Chinese, German, Japanese, Korean and Taiwanese [80–85]. Meta-analyses using both SNP rs505922 and blood types also support an association between non-O blood types and increased risk of pancreatic cancer [23,86]. Evaluation of blood groups across a spectrum of cancers revealed that the non-O blood types are associated with increased risk of exocrine pancreatic cancer but not with endocrine pancreatic cancer or any other cancer type studied, including stomach [19].…”
Section: Abo Gene Polymorphisms and Cancermentioning
confidence: 85%
“…Particularly, the most widely investigated SNPs of the ABO gene were rs505922 and rs657152 [12][13][14][15]. Meta-analysis that evaluated the relationship between rs505922 SNP and overall cancer have already been reported by Duan et al [16] four years ago.…”
Section: Introductionmentioning
confidence: 99%